THE EFFECT OF SERVICE QUALITY ON PARTICIPANT SATISFACTION AND ITS IMPACT ON PARTICIPANT LOYALTY OF BPJS KETENAGAKERJAAN NORTH MEDAN BRANCH - Laura Agustina Hasibuan; Sukaria Sinulingga; Linda T. Maas (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
As a company engaged in the field of social security for workers, BPJS Ketenagakerjaan carries out professionalism in providing services to all participants. Professional service is a major requirement for organizations in order to reach and retain their customers. In this case, one of the Employment BPJS customers is a participant. Even though it is mandatory for all workers in Indonesia, in reality the participation rate is still relatively low where data from 2016 – 2018 still shows unregistered workers at over 60% of the total workforce in Indonesia. The research was conducted using Path Analysis consisting of 5 independent variables (Reliability, Assurance, Tangibles, Empathy, Responsiveness), 1 dependent variable (Participant Loyalty) and 1 intermediate variable (Participant Satisfaction). The results showed that the direct effect of Service Quality had a positive and significant effect on the satisfaction of participants in the North Medan Employment BPJS. Likewise, the indirect effect of showing Participant Loyalty through Service Quality as an intermediate variable has a positive and significant effect on Participants Satisfaction of the North Medan Employment BPJS. Of the 5 (five) independent variables, the variables Reliability, Tangibles, Empathy and Responsiveness have a positive and significant effect on Participant Loyalty through Participant Satisfaction as an intermediate variable. Meanwhile, the Assurance variable has no positive and significant effect on Participant Loyalty through Participant Satisfaction as an intermediate variable.